Recent Progress in the Fabrication and Optical Properties of Nanoporous Anodic Alumina - Choudhari, Khoobaram S.; Choi, Chang-Hwan; Chidangil, Santhosh; George, Sajan D. (Nanomaterials (Basel, Switzerland), 2022)
The fabrication of a thick oxide layer onto an aluminum surface via anodization has been a subject of intense research activity for more than a century, largely due to protective and decorative applications. The capability to create well-defined pores via a cost-effective electrochemical oxidation technique onto the surface has made a major renaissance in the field, as the porous surfaces exhibit remarkably different properties compared to a bulk oxide layer. Amongst the various nanoporous structures being investigated, nanoporous anodic alumina (NAA) with well-organized and highly ordered hexagonal honeycomb-like pores has emerged as the most popular nanomaterial due to its wide range of applications, ranging from corrosion resistance to bacterial repelling surfaces. As compared to conventional nanostructure fabrication, the electrochemical anodization route of NAA with well-controlled pore parameters offers an economical route for fabricating nanoscale materials. The review comprehensively reflects the progress made in the fabrication route of NAA to obtain the material with desired pore properties, with a special emphasis on self-organization and pore growth kinetics. Detailed accounts of the various conditions that can play an important role in pore growth kinetics and pore parameters are presented. Further, recent developments in the field of controlling optical properties of NAA are discussed. A critical outlook on the future trends of the fabrication of NAA and its optical properties on the emerging nanomaterials, sensors, and devices are also outlined.